2016
DOI: 10.4028/www.scientific.net/kem.711.480
|View full text |Cite
|
Sign up to set email alerts
|

Fibre Cocktail to Improve Fire Resistance

Abstract: Favourable experience with fibre reinforced concrete (FRC) resulted in its increasing use worldwide. The properties of fibre reinforced concrete are mostly influenced by the type and the amount of fibres. Our experimental study was directed to the possible improvements of the residual flexural strength and the properties of concrete exposed to high temperatures with different fibre cocktails including steel, micro polymer or cellulose fibres. The influence of type and amount of fibres on residual flexural stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…This effect takes place because SF elongates at higher temperatures and creates extra stresses within the concrete. Several research findings showed that reducing the percentage of SF from 1% to 0.3% or 0.5% can reduce the effect of spalling [ 82 ]. The low amount of SF does not lead to a significant effect when the SF expands.…”
Section: Response Of Different Concrete Types Exposed To Elevated Tem...mentioning
confidence: 99%
See 2 more Smart Citations
“…This effect takes place because SF elongates at higher temperatures and creates extra stresses within the concrete. Several research findings showed that reducing the percentage of SF from 1% to 0.3% or 0.5% can reduce the effect of spalling [ 82 ]. The low amount of SF does not lead to a significant effect when the SF expands.…”
Section: Response Of Different Concrete Types Exposed To Elevated Tem...mentioning
confidence: 99%
“…A small SF percentage (limited fiber count) has limited contribution to the control of internal cracking. In turn, using a large percentage of steel fibers will reduce the overall strength and the modulus of elasticity of concrete [ 81 , 82 ]. At 500 °C, the SF fibers can be seen pulling out of the specimen, while at 800 °C, the fibers have melted completely and are not visible [ 81 ].…”
Section: Response Of Different Concrete Types Exposed To Elevated Tem...mentioning
confidence: 99%
See 1 more Smart Citation